Assessment of prenatal co-parenting relationship: adaptation of the "Parental Alliance Measure (PAM)" - Radovanovic, Mila; Mihic, Ivana (Primenjena psihologija, 2023)
Within the framework of parental roles, the partners achieve a special form of cooperation - coparenting, which is aimed at designing, managing and implementing joint care for children. The quality of the coparental relationship is important for the quality of parenting, but also for the development of the child, primarily in the domain of socio-emotional development, behavioral and relational competencies of the child. Longitudinal studies indicate that the quality of the coparental relationship prenatally is a good predictor of this relationship after the birth of the child. In the Serbian speaking area no research has been done so far in the field of coparental relations in the prenatal period, and accordingly there is no adequate assessment instrument. Taking into account the importance of research in this area for the development of the theory and practice of developmental and family psychology, the need for the adaptation of a questionnaire that would serve researchers and practitioners was recognized. The aim of this paper is to present the factor structure and basic psychometric characteristics of the adapted version of the Parenting alliance measure (Parenting alliance measure, Abidin & Konold 1999) on a sample of future parents. The sample consisted of 342 respondents, i.e. 171 couples expecting their first child. Factor analysis isolated three factors named as: mutual support of coparents, mutual involvement of coparents and shared values ​​of coparenting. Cronbach's alpha for the scale as a whole is 0.95, while for individual subscales it is: 0.89 for the subscale quality of mutual support, .89 for the subscale quality of mutual involvement of parents and .77 for the subscale of shared values ​​of co-parents. The adapted questionnaire showed good metric characteristics, which resulted in a representative instrument for assessing prenatal coparental cooperation.